Tradisi Elohis Dalam Tetrateukh - Osian Orjumi Moru (Institut Agama Kristen Negeri Toraja, 2020)
The Elohist tradition is a collection of writings which play an important role in the making of the books of Tentrateuch. This tradition was created in the northern region during the social revolution of the northern kingdom of Israel under the new government led by Jerobeam I. Based on the background, this article is written to give a whole understanding about both concept and context of Elohist tradition through qualitative research by using hermeneutics approach and literature study. This article is systematically and comprehensively explaining about the connection between Elohist tradition with the effort to succeed and legitimize the power of elites in Northern Kingdom of Israel. This article also describes the reality that Elohist tradition is a kind of product which stresses the intimate connection between religion traditions with the social-political conditions in the Northern Kingdom of Israel in 930 until 722 B.C. Based on this concept, the Elohist traditon is written with the main major is related with social-religious propaganda either in the global and local diplomatic context.